Improvement Of Tertiary Irrigation Networks And Their Impact On Farmers’ Income And Income Distribution - Nurman Yuliandry; R Wisnu Prio Pamungkas (ENCRYPTION: Journal of Information And Technology, 2025)
This study aims to determine the impact of improving tertiary irrigation networks through lining construction on farmers’ income and income distribution. The research was conducted in eight districts of West Java Province, namely Bandung, West Bandung, Subang, Purwakarta, Karawang, Indramayu, Bogor, and Cianjur. Primary data were collected through field surveys, interviews, and questionnaires, while secondary data were obtained from institutional records. Data analysis included the Shapiro–Wilk normality test, paired t- test, analysis of variance (ANOVA), financial feasibility analysis (NPV, IRR, B/C ratio), and the Gini Index for income distribution. The results showed that tertiary irrigation improvements in simple irrigation schemes generated the highest additional profit (IDR 786,000/ha/year) but were not statistically significant, while in semi-technical irrigation the additional profit of IDR 626,000/ha/year was significant at the 5% level. In technical irrigation, the additional profit was IDR 290,000/ha/year and not significant. The income distribution analysis indicated a slight improvement, with the Gini Index decreasing from 0.321 to 0.319, still within the moderate inequality category. Financially, the improvement projects were feasible with an average IRR of 18–24% and B/C ratios above 1.3.